Pemanfaatan Alumina Waste dari Tailing Bauksit Menjadi Zeolit Adsorben - Septiansyah, Sy Indra; Santi, Maya (EKSPLORIUM, 2018)
Alumina waste from bauxite tailings is the by products derived from bauxite ore beneficiation. The beneficiation process is done by separating the particles that exist such as mud or clay, roots, grain, bauxite ore ranges from 2 mm are discarded or be referred to as a waste product or tailings. High concentration of alumina and silica in bauxite tailings considered as one of the reasons why these tailings can be used as base material in the making new products, namely synthetic zeolites. Zeolites synthetic is selected because zeolites are imported, expensive and have uniform properties and >150 types of synthetic zeolites can be made commercially and even in industrial zeolite can be used widely as an adsorbent, ion exchange, membranes, catalysts, etc. The chemical analysis of bauxite tailings showed the composition of alumina (Al2O3) is approximately 49.41% silica (SiO2) is about 12.58%, hematite (Fe2O3) is approximately 10.6% and some other inorganic oxides are small amounts. The conversion process bauxite tailings into zeolite is carried out by caustic fusion method to extract the fusion (alumina precursor) followed by the addition of sodium silicate precursor with synthesis formula 1.2Na2O.0.5SiO2.0.5Al2O3.10H2O and crystallization products is carried out by the hydrothermal method at low temperatures with variable incubation period specified. The results showed that the zeolite synthesis of bauxite tailings using caustic fusion and followed by crystallization at low temperature and under atmospheric pressure has succeeded in transforming the product into an amorphous phase to the crystalline phase product zeolite adsorbent.